Cultural Leadership in Organizations - Trice, Harrison M.; Beyer, Janice M. (Organization Science, 1991)
Although there is general recognition that leadership is important for organizational cultures, the issue of how leadership affects culture has received only scattered attention. Existing analyses have tended to focus on how leaders create or change cultures, ignoring the role that leadership plays in maintaining cultures. This paper focuses on how cultural leadership that innovates, by either creating or changing organizational cultures, is likely to differ from that which maintains organizational cultures. Hypothesized linkages are advanced between nine elements of cultural leadership—drawn from the literature on charisma—and its consequences. The predictions made are derived from a synthesis of existing theory and insights gained from descriptions of leadership in the scholarly and popular literatures. Both descriptions and theoretical considerations suggest that, while cultural innovation and maintenance leadership differs in some ways, the behaviors of effective cultural leaders do not. Cultural leadership apparently has some generic characteristics. Two variants of each of the basic types are identified and linked to extant conceptualizations of leadership. Implications discussed include the risks and advantages of organizations' having multiple cultural leaders at the same time.